DETERMINAN PENDAPATAN ASLI DAERAH PADA KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Aris Eddy Sarwono (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to determine the factors that affect the Regional Original Income(PAD) in the district/city government in Central Java Province. These factorsinclude regional levies, advertisement taxes, parking taxes, restaurant taxes andland and building rights acquisition fees (BPHTB). This study uses secondarydata. The number of Observed in this study was 76 originating from 19Regencies/Cities in Central Java Province. The research period of this researchis the period 2015-2018. The research method used in this research is panel dataregression analysis with E-views. The results showed that regional levies had anegative and significant effect on PAD, while BPHTB had a significant positiveand significant effect on PAD. The advertisement tax, parking tax, and restauranttax variables have no significant effect on PAD. In addition, this study uses thecontrol variables of population and area. The test results show that thepopulation control variable can control the dependent variable (PAD). A largenumber of residents will increase the amount of PAD obtained by an area, whilethe control variable for area area cannot control the PAD variable. Suggestionsfor further researchers can discuss other factors that affect PAD